PENGARUHPRODUK PEMBIAYAAN MULTIGUNA TERHADAP MINAT NASABAH DI PT BANK SUMUT KANTOR CABANG SYARIAH MEDAN RINGROAD - Atang Gunawan; Syamsul Effendi (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
The purpose of this study is to determine the effect of multipurpose financing products on customer interest in using the services of PT Bank Sumut Syariah Medan Ringroad Branch Office, the factors that influence customers to choose multipurpose financing products at PT Bank Sumut Syariah Medan Ringroad Branch Office, and the benefits of multipurpose financing products for customers. at PT Bank Sumut Syariah Branch Office Medan Ringroad. The research technique used is probability sampling technique with the sampling used is simple random. The data collection technique used is a questionnaire (questionnaire), analyzed using SPSS (Statistical Product and Service Solution). The results of the study show that: 1) Multipurpose Financing Products have a significant effect on customer interest in using the services of PT Bank Sumut Syariah Branch Office Medan Ringroad. This is evidenced by the t-test, the value of tcount is 6655 ttable 1.701. This also indicates that the variable of customer interest in using the services of PT Bank Sumut Syariah Branch Office Medan Ringroad can be explained by the multipurpose financing product variable of 59.9%, the remaining 40.1% is explained by other variables outside the study; 2) The factors that influence customers to choose multipurpose financing products at PT Bank Sumut Syariah Medan Ringroad Branch include religious factors, social factors, personal factors, cultural factors, and psychological factors. they choose the multipurpose financing product. Dominant factors influencing customers to choose these products are personal factors where for their needs in fulfilling life needs and for other interests it is personal and they make loans according to their needs or there are urgent needs; and 3) Benefits of Multipurpose Financing Products for Customers at PT Bank Sumut Syariah Medan Ringroad Branch Office, among others: avoiding usury, based on Islamic Sharia, profits are given based on profit sharing, guaranteed by the Deposit Insurance Corporation (LPS), Sharia Banks are equipped with Net Banking facilities , the profit sharing system is more fair and transparent, imposes a low savings balance, the customer is a partner of the bank, the customer's funds are used in accordance with sharia, there is an early warning about danger due to its transparent nature, the funds are intended for the benefit and benefit of the people